Forward Osmosis with a Novel Thin-Film Inorganic Membrane - You, Shijie; Tang, Chuyang; Yu, Chen; Wang, Xiuheng; Zhang, Jinna; Han, Jia; Gan, Yang; Ren, Nanqi (Environmental science & technology, 2013)
Forward osmosis (FO) represents a new promising membrane technology for liquid separation driven by the osmotic pressure of aqueous solution. Organic polymeric FO membranes are subject to severe internal concentration polarization due to asymmetric membrane structure, and low stability due to inherent chemical composition. To address these limitations, this study focuses on the development of a new kind of thin-film inorganic (TFI) membrane made of microporous silica xerogels immobilized onto a stainless steel mesh (SSM) substrate. The FO performances of the TFI membrane were evaluated upon a lab-scale cell-type FO reactor using deionized water as feed solution and sodium chloride (NaCl) as draw solution. The results demonstrated that the TFI membrane could achieve transmembrane water flux of 60.3 L m–2 h–1 driven by 2.0 mol L–1 NaCl draw solution at ambient temperature. Meanwhile, its specific solute flux, i.e. the solute flux normalized by the water flux (0.19 g L–1), was 58.7% lower than that obained for a commercial cellulose triacetate (CTA) membrane (0.46 g L–1). The quasi-symmetry thin-film microporous structure of the silica membrane is responsible for low-level internal concentration polarization, and thus enhanced water flux during FO process. Moreover, the TFI membrne demonstrated a substantially improved stability in terms of mechanical strength, and resistance to thermal and chemical stimulation. This study not only provides a new method for fabricating quasi-symmetry thin-film inorganic silica membrane, but also suggests an effective strategy using this alternative membrane to achieve improved FO performances for scale-up applications.